2013
DOI: 10.3126/joim.v34i3.8917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin diseases and impact on quality of life in hilly region of Nepal

Abstract: Introduction: Skin diseases (SDs) are one of the most common health problems in Nepal. The objectives of this study are to determine the prevalence of SDs and impact on quality of life (QoL) in a rural community in Nepal. Methods: A house-to-house survey was conducted in a community with 3,207 inhabitants, to obtain socio-demographic data and identify individuals with SDs. Free examination and treatment was offered at 4 health camps. Individuals with long-standing SDs were interviewed using the Dermatology Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…[22] Similarly, Shrestha and colleagues reported a mean DLQI score of 10.7 (range 7-19) among their study respondents, indicating a large impact on QoL. [23] Quality of life in skin disorders was also heavily impaired in studies reported from Saudi Arabia [24] , Brazil [25] , India [26] and other parts of the world. [27] It is mention that against to our study criteria, the above mentioned studies were conducted on a disease specific population.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Similarly, Shrestha and colleagues reported a mean DLQI score of 10.7 (range 7-19) among their study respondents, indicating a large impact on QoL. [23] Quality of life in skin disorders was also heavily impaired in studies reported from Saudi Arabia [24] , Brazil [25] , India [26] and other parts of the world. [27] It is mention that against to our study criteria, the above mentioned studies were conducted on a disease specific population.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, eczemas are the commonest with high prevalence of allergic contact dermatitis (ACD) [1]. Because of diversity in genetic, environment, topography and occupation of Nepalese population, these factors may also influence the exposure patterns and could be responsible for the variations in the patterns of skin reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The annual report of the Department of health services in 2067/068 (2010/2011 A.D) ranks skin diseases as the fourth most common problem in patients attending outpatient clinics in the country, and comprises 1.4 % of the total in-patient morbidity. 1 According to the data of a referral hospital in Kathmandu, in the year 2008, skin diseases accounted 10.5% (34,360) of total out-patient department (3,25,920). 2 However, a community study which surveyed a rural population of 3207 inhabitants showed an overall skin disease prevalence of 20.1 %.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, a community study which surveyed a rural population of 3207 inhabitants showed an overall skin disease prevalence of 20.1 %. 3 Information on community based prevalence and pattern of skin diseases would be a better measure of burden due to skin diseases in the general population in order to assist in planning of possible intervention strategies.…”
Section: Introductionmentioning
confidence: 99%